Finland: Environmental History in National Languages - Timo Myllyntaus (White Horse Press, 2022)
For some time, the journal Environment and History has published Notepad surveys on the development of the research on environmental history in the national languages. I was asked to work out a review of the recent trends in Finland. In this survey, I attempt to relate to the current developments to my earlier observations on the Finnish printing industry since the 1840s presented in my Licentiate thesis. This theme touches upon the debate ongoing for almost two centuries over which languages are mature enough for scientific expression and what scientific expression requires from a language. Diverse scientific publishing activities are considered a strong indication of the sophistication of the language. This essay focuses on a rather narrow sector both thematically and temporally: on environmental history books published in national languages around 2013-2020. The article states that the predominant language of environmental history in Finland has changed from Swedish to Finnish in recent decades, while the topics of environmental history have expanded and the writing community has diversified. Nowadays, non-professional historians publish a great proportion of books on environmental history. During the period under review, the main themes in Finnish environmental history have been forests, water, climate and weather, animals, conflicts of interests and the conservation of nature.